2021
DOI: 10.1089/jpm.2020.0718
|View full text |Cite
|
Sign up to set email alerts
|

Dying Alone during a Pandemic

Abstract: Background: The coronavirus disease 2019 pandemic is an unprecedented experience that has had profound impact and consequences for health care providers, visitation policies, and procedures. Hospitals and health care facilities were forced to implement changes to visitation policies, in an effort, to minimize transmission of the virus, which unfortunately had negative impact on patients' and family members' well-being as well as moral distress for the staff. Objectives: We present here a case illustration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Capozzo (2020) argues that, even in a pandemic, it is not acceptable to have to die alone, and that fear and anxiety are heightened if one is alone while being sick, hospitalised, or dying. The negative impact of isolation on the patient, hospital staff, and family members was demonstrated by Ann-Yi et al (2021), who found that patients regarded the well-being of their loved ones as the second most important priority for their well-being. In a survey by Carson et al (2021) which focused on the impact of losing a loved one during the pandemic, findings indicated that posttraumatic stress increased dramatically, while post-traumatic growth was very low.…”
Section: Introductionmentioning
confidence: 99%
“…Capozzo (2020) argues that, even in a pandemic, it is not acceptable to have to die alone, and that fear and anxiety are heightened if one is alone while being sick, hospitalised, or dying. The negative impact of isolation on the patient, hospital staff, and family members was demonstrated by Ann-Yi et al (2021), who found that patients regarded the well-being of their loved ones as the second most important priority for their well-being. In a survey by Carson et al (2021) which focused on the impact of losing a loved one during the pandemic, findings indicated that posttraumatic stress increased dramatically, while post-traumatic growth was very low.…”
Section: Introductionmentioning
confidence: 99%